Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Non-native vegetation encroachment drives trophic turnover in island nematodes - Adam Sharp; Margarida Correia; Alan Gray; Rebecca Lawson; Martha Ledger; Noel Tawatao; Thomas Prior (Biodiversity and Conservation, 2025)
Nematodes are important components of terrestrial ecosystems. There is currently limited understanding of how soil nematode communities are altered by non-native vegetation encroachment. The spatial turnover of nematode communities was studied on Ascension Island in the South Atlantic: an isolated and degraded volcanic island of sparse native vegetation. Many non-native plants were introduced in the mid-1800’s, and non-native shrubs have more recently spread across the lowlands. Ascension’s elevation gradient represented a unique space-for-time proxy for non-native vegetation colonisation of a relatively barren landscape. Nematodes were collected at 0, 200, 400, 600 and 800 m elevations along three transects and their community composition linked to Landsat-derived vegetation cover and moisture over the 2000–2023 period. Although taxonomic turnover was elevation independent, both nematode abundance and richness increased with elevation. The moist and densely-vegetated mountain top was dominated by plant-root parasites, less dense mid-elevations by omnivores, dry and sparsely-vegetated lowlands by fungivores, and the moist littoral habitat by predators. Landsat analysis predicted that the relative abundance of root parasitic nematodes on Ascension increased by 23% with spreading non-native vegetation over 24 years. While taxonomic turnover in nematode composition may be resultant solely of historic species introductions, trophic turnover is spatially structured and likely follows non-native vegetation encroachment closely. Root parasitic nematodes may be spreading rapidly with non-native vegetation, especially on oceanic islands. The abundance of such nematodes in soil could become an unanticipated hinderance in the restoration of invaded habitat – potentially requiring management long after non-native vegetation is cleared.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Invasive vegetation encroachment modulates dual threats faced by island-endemic scaly crickets - Weng Yuen Chin; Vicky Wilkins; Adam Sharp (Biological Invasions, 2024)
The mechanisms by which non-native species impact island-endemic populations are varied and often convoluted. For effective invertebrate conservation where capacity is limited, it is vital to understand both direct and indirect species interactions. Those interactions define specific threats and therefore highlight possible solutions. We quantified several of the non-native species threats faced by an endemic scaly cricket, Discophallus ascension (family: Mogoplistidae), found on Ascension Island’s naturally barren coastlines. We hypothesized that encroaching non-native Mexican thorn Prosopis juliflora (1) directly reduced microclimate suitability, (2) indirectly increased resource competition with non-native species, and (3) indirectly increased non-native predation. Our aim was to assess how rapidly spreading Mexican thorn might reduce endemic cricket populations. Lab trials first confirmed the temperature and diet preferences of D. ascension. Mexican thorn significantly increased ground-level temperature but not above the estimated optimum for D. ascension within key habitat. Observed interspecific resource competition was significantly greater in habitat degraded by Mexican thorn and was driven by non-native ants, house crickets Gryllodes sigillatus and cockroaches Periplaneta americana . Recorded cricket predation was almost entirely by non-native rats Rattus rattus in barren habitat but primarily by ants in Mexican thorn habitat. Threats to D. ascension were therefore modulated by invasive vegetation, but driven by non-native insects and rats at all sites. We conclude that removal of vegetation alone is likely to reduce resource competition but not predation. Managing multiple invasive species is likely necessary for successful species conservation.

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Heavy metal removal by the photosynthetic microbial biomat found within shallow unit process open water constructed wetlands - Zhaoxun Yang; Sarah M. Acker; Adam R. Brady; Armando Arenazas Rodríguez; Lino Morales Paredes; Juana Ticona; Giuliana Romero Mariscal; Gary F. Vanzin; James F. Ranville; Jonathan O. Sharp (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Larval influx of Diadema antillarum to the Florida Keys linked to passage of a Tortugas Eddy - Colette J. Feehan; William C. Sharp; Travis N. Miles; Michael S. Brown; Diane K. Adams (Coral Reefs, 2019)

Pharmacological evidence that 5-HT2C receptor blockade selectively improves decision making when rewards are paired with audiovisual cues in a rat gambling task - Wendy K. Adams; Chris Barkus; Jacqueline-Marie N. Ferland; Trevor Sharp; Catharine A. Winstanley (Psychopharmacology, 2017)

Fertilization limitation of Diadema antillarum on coral reefs in the Florida Keys - Colette J. Feehan; Michael S. Brown; William C. Sharp; Jean‐Sébastien Lauzon‐Guay; Diane K. Adams (Ecology, 2016)
Mass mortality of the sea urchin Diadema antillarum due to disease outbreaks in 1983 and 1991 decimated populations in the Florida Keys, and they have yet to recover. Here, we use a coupled advection–diffusion and fertilization–kinetics model to test the hypothesis that these populations are fertilization limited. We found that fertilization success was ≥ 96% prior to the first disease outbreak, decreased substantially following recurrent disease to 3%, and has since remained low. By investigating the combined effects of physical factors (population spatial extent and current velocity) and sea urchin behavior (aggregation) on density‐dependent fertilization success, we show that fertilization success at a given density increases with increasing population spatial extent and decreasing current velocity, and is greater under simulated aggregation behavior of D. antillarum . However, at present population densities, the increase in fertilization success due to aggregation is D. antillarum restocking program to obtain reproductively viable populations.

Complex carbon cycle responses to multi‐level warming and supplemental summer rain in the high A rctic - Elizabeth D. Sharp; Patrick F. Sullivan; Heidi Steltzer; Adam Z. Csank; Jeffrey M. Welker (Global Change Biology, 2013)
The Arctic has experienced rapid warming and, although there are uncertainties, increases in precipitation are projected to accompany future warming. Climate changes are expected to affect magnitudes of gross ecosystem photosynthesis ( GEP ), ecosystem respiration ( ER ) and the net ecosystem exchange of CO 2 ( NEE ). Furthermore, ecosystem responses to climate change are likely to be characterized by nonlinearities, thresholds and interactions among system components and the driving variables. These complex interactions increase the difficulty of predicting responses to climate change and necessitate the use of manipulative experiments. In 2003, we established a long‐term, multi‐level and multi‐factor climate change experiment in a polar semidesert in northwest G reenland. Two levels of heating (30 and 60 W m −2 ) were applied and the higher level was combined with supplemental summer rain. We made plot‐level measurements of CO 2 exchange, plant community composition, foliar nitrogen concentrations, leaf δ 13 C and NDVI to examine responses to our treatments at ecosystem‐ and leaf‐levels. We confronted simple models of GEP and ER with our data to test hypotheses regarding key drivers of CO 2 exchange and to estimate growing season CO 2 ‐C budgets. Low‐level warming increased the magnitude of the ecosystem C sink. Meanwhile, high‐level warming made the ecosystem a source of C to the atmosphere. When high‐level warming was combined with increased summer rain, the ecosystem became a C sink of magnitude similar to that observed under low‐level warming. Competition among our ER models revealed the importance of soil moisture as a driving variable, likely through its effects on microbial activity and nutrient cycling. Measurements of community composition and proxies for leaf‐level physiology suggest GEP responses largely reflect changes in leaf area of S alix arctica , rather than changes in leaf‐level physiology. Our findings indicate that the sign and magnitude of the future High A rctic C budget may depend upon changes in summer rain.